Sécurité pharmaceutique, technologie et marché en Afrique - Mathieu Quet (Revue d'anthropologie des connaissances)
The article deals with the issue of illicit medicines and with the ways in which the Kenya government fights against it. It pays particular attention to the recent redefinition of the problem and to the growing importance taken by technologies for the securitization of pharmaceutical markets. The hypothesis discussed is that the current conception and technical tooling of the fight against illicit medicines participates in a shift of debates regarding access to medicines in the global South. Increasingly, these debates will have to take into account the role of standards and technologies of control in the (il)legitimation of pharmaceutical flows. To this end, the analysis compares different technologies of security and shows their underlying conceptions of authenticity and of pharmaceutical legitimacy.